ANALISIS KESULITAN SISWA SMP DALAM MATERI BANGUN RUANG SISI DATAR BERBANTUAN GOOGLE CLASSROOM - Mira Mardia; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research describes students' difficulties in learning mathematics, the research was conducted at SMPN 1 CIHAMPELAS class IX with the material  build  room  side  flat  assisted by google classroom. The approach  in this research  uses a  qualitative  approach. The instrument used is a description test which amounts to 7 questions with different difficulty levels collected through google classroom. Google Classroom is a learning application released by Google. The ease of access via computers and mobile phones is very beneficial for teachers and students in schools. The goal is to describe blended learning, google classroom as an alternative in learning, and blended learning through google classroom. difficulty in calculating the surface area of a cube, as many as 33.34% of students have difficulty in calculating the surface area of a prism, as many as 33.60% of students have difficulty in calculating the surface area of a pyramid, as many as 11.12% of students have difficulty in calculating the volume of a cuboid, 20.75% of students still have difficulty in calculating the volume of a prism, and as many as 57.78% of students had difficulty solving problems involving the diagonal of the space, the diagonal of the plane, and the diagonal of the plane.